Endemicity of dengue in Mamund Subdivision, District Bajaur, Pakistan, in 2022 - Zeb, Khan (Infectious Diseases Journal of Pakistan, 2025)
Background: Dengue, a rapidly rising mosquito-borne viral disease, threatens nearly half of the global population. It is endemic in many regions of Pakistan, including Khyber Pakhtunkhwa. Despite frequent reports from Mamund, District Bajaur, its endemic status has not been evaluated, raising the question of whether cases originate locally or are imported. Material and Methods: A descriptive cross-sectional study was conducted at Government Category-D Hospital Mamund from September to December 2022. A total of 230 patients aged 10–70 years with suspected or confirmed dengue were enrolled through consecutive non-probability sampling. Data on demographics, travel history, and dengue NS1 results were collected, while patients without consent, outside the age range, or lacking NS1/travel history were excluded. Analysis was performed using SPSS. Results: Of the 230 patients, 144 (62.6%) were male and 86 (37.4%) female. Mean age was 30.9 ± 11 years. Travel history outside Mamund was present in 129 (56.1%) and absent in 101 (43.9%). NS1 positivity was found in 110 patients (47.8%), all of whom had recent travel history. No patient without travel history tested NS1 positive. The association between travel history and NS1 positivity was statistically significant (p < 0.001). Conclusion: Dengue cases in Mamund subdivision appear imported, with no evidence of endemic local transmission. Findings emphasize the need for vector surveillance studies to confirm the presence or absence of Aedes mosquitoes in Mamund and to guide preventive strategies. Keywords: Aedes, Bajaur, Dengue, Endemicity, Epidemiology, Mamund, NS1 Protein, Pakistan.